The Quadratic Specht Triangle (Journal of Computational Mathematics, 2020)
We propose a class of 12 degrees of freedom triangular plate bending elements with quadratic rate of convergence. They may be viewed as the second order Specht triangle, while the Specht triangle is one of the best first order plate bending elements. The convergence result is proved under minimal smoothness assumption on the solution. Numerical results for both the smooth solution and nonsmooth solution confirm the theoretical prediction.
Keywords: Specht triangle; Plate bending element; Basis functions.